Mapping the big picture of mental health literacy in education: a bibliometric analysis - Shengnan Zeng; Richard Bailey; Ra’ed Ali Alkhamaiseh; Shuo Peng; Nadia Samsudin (Humanities & Social Sciences Communications)
Abstract Mental health literacy is increasingly recognised as a key component in promoting mental health and reducing stigma, yet comprehensive bibliometric assessments of this field remain scarce. This study aims to explore and synthesise the current state of mental health literacy research through bibliometric analysis. Publication trends, influential authors, prolific journals, international collaboration, key terms, and indicators are examined. A systematic search was conducted using the Scopus database for literature from 2000 to 2023. Descriptive and bibliometric analyses were performed to examine the dataset. Interest in mental health literacy research has significantly increased since 2015. Jorm and Kutcher were identified as influential authors in the field. Australia and the United States demonstrated strong collaboration. International Journal of Environmental Research and Public Health and BMC Psychiatry were the most prolific journals. Key terms and indicators in mental health literacy research shifted to education and interventions, forming seven research clusters. While limited to Scopus-indexed documents, the study offers valuable insights for researchers, educators, and policymakers. The findings provide a foundation for developing targeted interventions, educational programmes, and public health strategies to improve mental health worldwide. This is the first known study to report a bibliometric analysis of MHL using VOSviewer and Biblioshiny.